ECOTECT SIMULATION: ADVANCING ENVIRONMENTAL RESPONSIVENESS IN NATURE-BASED SCHOOL CONCEPTUAL DESIGN - Aliyah, Nur; Dewi, Tiara Rukmaya (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2024)
Balikpapan City focuses on the vision and mission of zero carbon emissions. One way to achieve this is to provide facilities with a sustainable natural school system with a green architectural approach. Students learn to care for ecosystems through hands-on, immersive experiences.This research aims to obtain an optimal building design in response to the local climate to create user comfort in learning activities. A learning building must support a learning objective focusing on acquiring specific skills, knowledge, or competencies in a particular subject. Geographically, the design location is in a wet tropical sub-climate, so the potential for sunlight can be utilized as an alternative source of renewable energy in buildings. This research uses Ecotect simulations during the design process to ensure the schools are sustainable and environmentally friendly with a focus on ecological aspects and building performance.This research uses quantitative methods to measure solar paths, radiation intensity, and shading indicators. The data collected guides the design process and creates energy-efficient and well-suited buildings to their environment. By integrating these insights from the beginning, nature-based schools in Balikpapan can become sustainability models, offering students an education deeply rooted in their natural surroundings. The results of this research are that the tropical climate at the design location can be used as an energy alternative in natural school buildings. However, the choice of building shape is a consideration in the design process because the shape of the building can influence the desired output.